2019
DOI: 10.1016/j.cub.2019.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms for Visual and Motor-Related Astrocyte Responses in Mouse Visual Cortex

Abstract: SummaryAstrocytes are a major cell type in the mammalian nervous system, are in close proximity to neurons, and show rich Ca2+ activity thought to mediate cellular outputs. Astrocytes show activity linked to sensory [1, 2] and motor [3, 4] events, reflecting local neural activity and brain-wide neuromodulatory inputs. Sensory responses are highly variable [5, 6, 7, 8, 9, 10], which may reflect interactions between distinct input types [6, 7, 9]. However, the diversity of inputs generating astrocyte activity, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 53 publications
10
74
0
Order By: Relevance
“…Besides their supportive role in terms of metabolism, astrocytes were shown to influence information processing and cognition by integrating local sensory information and behavioral state (Hallmann et al., 2017; Lima et al., 2014; Oksanen et al., 2019; Peteri et al., 2019; Slezak et al., 2019). In response to glucocorticoids, resetting of the circadian clock via non‐canonical pathways (Suchmanova et al., 2019) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their supportive role in terms of metabolism, astrocytes were shown to influence information processing and cognition by integrating local sensory information and behavioral state (Hallmann et al., 2017; Lima et al., 2014; Oksanen et al., 2019; Peteri et al., 2019; Slezak et al., 2019). In response to glucocorticoids, resetting of the circadian clock via non‐canonical pathways (Suchmanova et al., 2019) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical astrocytes show differential responses to the metabotropic agonist phenylephrine, which reflect the distribution of morphologically and transcriptomically distinct astrocyte populations [63]. Finally, work from our own lab suggests that local synaptic activity as well as the behavioral state of the animal are crucial in shaping intracellular Ca 2+ signaling in the mouse visual cortex, suggesting that astrocytes act as signal integrators to produce distinct physiological effects [82]. This is in agreement with previous work showing the effects of the neuromodulator noradrenaline on astrocyte signaling [91].…”
Section: Physiological Heterogeneitymentioning
confidence: 91%
“…Recent studies, however, have taken advantage of the fact that genetically encoded calcium indicators (GECIs) can be expressed in a cell type specific manner and targeted to specific subcellular locations. They have revealed a rich diversity of Ca 2+ signals in cells, ranging from the generation of signaling microdomains [79][80][81] through to global waves that encompass entire astrocytes, including their cell bodies [81,82]. Ca 2+ responses may be spontaneous [79,83] or evoked by neuronal activity [25,26], with differences between brain regions reported; striatal and hippocampal astrocytes show differences in these two forms of Ca 2+ signal [15].…”
Section: Physiological Heterogeneitymentioning
confidence: 99%
“…Recent evidences highlight important roles of astroglia in regulating neural activity, brain states, and animal behavior, both in vertebrates (Brancaccio, Patton, Chesham, Maywood, & Hastings, 2017) and invertebrates (Ma, Stork, Bergles, & Freeman, 2016). Studies in rodents showed that astroglial cells are highly dynamic components of the brain, which respond to locomotion (Nimmerjahn, Mukamel, & Schnitzer, 2009; Sekiguchi et al, 2016; Slezak et al, 2019) or sensory stimulation (Gu et al, 2018; Slezak et al, 2019) with prominent changes in astroglial calcium levels and can regulate learning (Adamsky et al, 2018; Corkrum et al, 2020) or other state transitions (Bojarskaite et al, 2019; Cui et al, 2018; Oe et al, 2020; Poskanzer & Yuste, 2016) in the brain. Norepinephrine (Bekar, He, & Nedergaard, 2008; Oe et al, 2020; Salm & McCarthy, 1990; Shao & McCarthy, 1997) and acetylcholine (Araque, Martin, Perea, Arellano, & Buno, 2002; Pabst et al, 2016; Takata et al, 2011) are proposed to be the primary triggers for activating astroglia, yet several other molecules including glutamate (Hamilton et al, 2008; Mothet et al, 2005; Sun et al, 2013) play prominent roles in astroglial physiology.…”
Section: The Role Of Astroglia In Neural Circuit Function and Animal mentioning
confidence: 99%